Internal Stakeholders’ Contribution to Building Collapse in Lagos State, Nigeria: A Perceptual Survey - Olumide Afolarin Adenuga; Innocent Chigozie Osuizugbo; Ikhelo Benedict Imoesi (Civil and Sustainable Urban Engineering, 2022)
Building collapse is a universal problem that has resulted in disruption, loss of lives and capital costs, as well as negatively affecting the image of the construction industry and its practitioners. The current study seeks to achieve the following objectives: (i) to assess the contributing factors of internal stakeholders to building collapse due to challenges faced in Lagos state, Nigeria; (ii) to determine the remedies to challenges faced by internal stakeholders towards reducing the spate of building collapses in the study area. The study adopted a survey research method. Questionnaires were administered to purposively selected internal stakeholders in the Nigerian construction industry within Lagos state. 127 questionnaires were administered to survey participants. The data collected was analysed using descriptive and inferential statistics. The results revealed a lack of consideration of life cycle costing of utilities, lighting and lifts; lack of proper integration and coordination of design elements; failure to consider the buildability and maintenance requirements during the design; absence of proper supervision and site inspections for quality checks; and failure to inspect materials storage on site, with their mean scores of 4.18, 4.11, 4.10, 4.10, and 4.10, respectively, as the top five contributing factors of internal stakeholders to building collapse in Lagos state. The study provided in-depth insight into the contributing factors of internal stakeholders to building collapse that can help construction professionals and stakeholders facilitate the development of strategies required to minimize the contributing factors of internal stakeholders to building collapse in the construction sector.